Hospitalized children with COVID-19 confirmed: A pilot study - Hariati, Suni; Erfina; Nurmaulid; Kadar, Kusrini Semarwati; Andriani; Hasniar (Pediomaternal Nursing Journal, 2023)
Introduction: The number of children confirmed with COVID-19 in Indonesia remains high compared to other countries (12.2%). 13.6% of all cases are hospitalized in quarantine rooms. This study aims to describe children with confirmed COVID-19 who have been hospitalized in Makassar, Indonesia.Methods: This pilot study was conducted in Makassar City, one of the cities in Indonesia with a high number of COVID-19 cases, in October 2021. A total of 25 children participated through consecutive sampling. This study consisted of children hospitalized in January-August 2021 who had confirmed COVID-19 and were admitted to quarantine or non-quarantine rooms. Inclusion criteria were children under 18 years old and parents who volunteered to complete the questionnaire based on COVID-19 prevention and control guidelines. The questionnaire focused on child and parent characteristics, COVID-19 symptoms, and the number of confirmed cases. Results: Of the 25 children hospitalized with confirmed COVID-19, 76% were hospitalized in quarantine rooms, 72% were boys, and their ages ranged from 0 to 13 years. The average number of siblings was 2.64±1.63, and the average length of hospital stay was 7.88±3.03 days. The most common symptoms were fever (68%), cough (44%), and diarrhea (28%). The majority of children had two symptoms (40%), were confirmed with COVID-19 once (84%), and were hospitalized one time (95%).Conclusions: The main characteristics of hospitalized children with confirmed COVID-19 are non-school age and boys. They have multiple symptoms, and fever is the most common. A holistic approach to treating all children hospitalized with COVID-19 should be taken. This study can be used as a baseline for formulating strategies and guidelines for preventing prolonged effects and treating hospitalized children with COVID-19.Keywords: COVID-19 in children; confirmed children; COVID-19 symptom; hospitalized children